Prevalence and patterns of multimorbidity among adults in rural Shanxi Province, China: A post-hoc exploratory subgroup analysis of a cross-sectional study - Shuai Tang; Yanxing Li; Runlan Li; Hongmei Yang; Tianyou Hao; Maoyi Tian; Xinyi Zhang; Xiangxian Feng; Zhifang Li (PLoS ONE, 2025)
Background In China, the prevalence of chronic diseases is increasing, especially in rural areas, affecting younger populations and associating with multimorbidity. However, in resources-limited rural areas, there is a lack of primary data to the prevalence and patterns of multimorbidity in young populations. This study aims to analysis the differences in multimorbidity prevalence and patterns across different age groups and genders among adults in rural Shanxi Province. Methods This study was a post-hoc analysis of a completed cross-sectional study. All the participants included in this post-hoc analysis were randomly selected from 80 villages from Shanxi Province. Multimorbidity, defined as the coexistence of two or more diseases in same individual, was assessed by collecting primary data (questionnaires and physical examinations) and routine data (health insurance claims and hospital electronic records). Results A total of 2,208 participants were included, with a mean age of 57.7 ± 10.5 years. 1283 (58.1%) were aged 30–59 years and 1152 (52.2%) were females. There were 1524 cases (69.0%) with disease and 818 cases (37.5%) with multimorbidity. Hypertension had the highest prevalence (43.5%) as well as multimorbidity pattern was often associated with it (75.3%). The three most common dyad multimorbidity patterns were hypertension and stroke, heart disease, and chronic digestive diseases, respectively. Among 30–59 years, it was hypertension respectively and stroke, chronic digestive diseases, and arthritis, while among ≥60 years, it was hypertension respectively and stroke, heart disease, and diabetes. In males, it was hypertension respectively and stroke, heart disease, and chronic digestive diseases, while in females it was hypertension respectively and arthritis, chronic digestive diseases, and diabetes. Conclusion The multimorbidity prevalence among adults in rural Shanxi Province is notably high. The pattern of multimorbidity is distinct differences between age groups and genders, suggesting that prevention and management of priority diseases in specific populations should be targeted.